2014
DOI: 10.1111/bph.12765
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of impaired adipose tissue methylation status and lipolytic response contributes to hepatoprotective effect of betaine in a mouse model of alcoholic liver disease

Abstract: BACKGROUND AND PURPOSEOveractive lipolysis in adipose tissue contributes to the pathogenesis of alcoholic liver disease (ALD); however, the mechanisms involved have not been elucidated. We previously reported that chronic alcohol consumption produces a hypomethylation state in adipose tissue. In this study we investigated the role of hypomethylation in adipose tissue in alcohol-induced lipolysis and whether its correction contributes to the well-established hepatoprotective effect of betaine in ALD. EXPERIMENT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…In the current study, our results showed that betaine supplementation decreased fatty acid synthesis and increased TG breakdown, which led to a decrease of hepatic lipid accumulation. These results are in line with previous studies which showed decreased TG content in the liver upon increasing betaine availability on adult mice [9,11]. In addition, studies also suggested that the effects of betaine on hepatic lipid deposition might also be through its ability to increase endogenous carnitine, as carnitine might increase carnitine palmitoyltransferase I-mediated fatty acid translocation into the mitochondria and β-oxidation [6,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, our results showed that betaine supplementation decreased fatty acid synthesis and increased TG breakdown, which led to a decrease of hepatic lipid accumulation. These results are in line with previous studies which showed decreased TG content in the liver upon increasing betaine availability on adult mice [9,11]. In addition, studies also suggested that the effects of betaine on hepatic lipid deposition might also be through its ability to increase endogenous carnitine, as carnitine might increase carnitine palmitoyltransferase I-mediated fatty acid translocation into the mitochondria and β-oxidation [6,22].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, studies also suggested that the effects of betaine on hepatic lipid deposition might also be through its ability to increase endogenous carnitine, as carnitine might increase carnitine palmitoyltransferase I-mediated fatty acid translocation into the mitochondria and β-oxidation [6,22]. Recently, the effects of betaine on the rectification of DNA methylation have also been declared to be a major mechanism accounting for the hepatoprotective effects of betaine [9,30]. These effects of betaine were mostly due to its role in one-carbon metabolism as a methyl donor.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, we provided evidence supporting that intracellular hypomethylation status in adipocytes in the setting of chronic alcohol feeding contributes to adipose tissue hyper-lipolytic response in ALD via suppressing protein phosphatase 2A(PP2A) activity, leading to hormone sensitive lipase over activation (Figure 2). 34 Our data support that rectification of methionine metabolism through dietary supplementation of betaine protects against alcohol-induced liver damage, at least partially via improving adipose tissue function. Taken together, the recent research in our group suggests that aberrant methionine metabolism in adipocytes contributes to alcohol-elicited adipose tissue dysfunction and liver damage.…”
Section: Aberrant Adipose Methionine Metabolism and Hyperlipolysis Insupporting
confidence: 67%
“…Further studies have reported that alcohol-induced decreases in the adipose SAM:SAH ratio and elevations in homocysteine levels [155, 156, 158, 159] enhances HSL activation to promote LD lipolysis [158160]. More importantly, betaine exerts it therapeutic effect to facilitate TAG storage in adipocytes by preventing these ethanol-induced changes in adipose tissue [158, 159].…”
Section: Changes In Adipocyte Lds After Ethanol Administrationmentioning
confidence: 99%